Adiabaticity parameters for the categorization of light-matter interaction: From weak to strong driving - Heide, Christian; Boolakee, Tobias; Higuchi, Takuya; Hommelhoff, Peter (Physical Review A, 2021)
We investigate theoretically and numerically the light-matter interaction in a two-band system (TBS) as a model system for excitation in a solid-state band structure. We identify five clearly distinct excitation regimes, categorized with well-known adiabaticity parameters: (1) the perturbative multiphoton absorption regime for small driving field strengths, and four light-field-driven regimes, where intraband motion becomes important (2) the impulsive Landau-Zener (LZ) regime, (3) the nonimpulsive LZ regime, (4) the adiabatic regime, and (5) the adiabatic-impulsive regime for large electric field strengths. This categorization is tremendously helpful to understand the highly complex excitation dynamics in solids, in particular, when the driving field strength varies, and this categorization naturally connects Rabi physics with Landau-Zener physics. In addition, we find an insightful analytical expression for the photon orders connecting the perturbative multiphoton regime with the light-field-driven regimes. Moreover, in the adiabatic-impulsive regime, adiabatic motion and impulsive LZ transitions are equally important, leading to a broken symmetry of the TBS and a residual current when applying few-cycle laser pulses of broken temporal symmetry. This categorization allows a deep understanding of strong-field excitation in solids, including current and high-harmonic generation in a large variety of settings, and will help to find optimal driving parameters for a given purpos
Keywords: light-matter interaction; two-band system; adiabaticity parameter; Rabi physics; Landau-Zener physics

Attosecond-fast internal photoemission - Heide, Christian; Hauck, Martin; Higuchi, Takuya; Ristein, Jürgen; Ley, Lothar; Weber, Heiko B.; Hommelhoff, Peter (Nature Photonics, 2020)
The photoelectric effect has a sister process relevant in optoelectronics called internal photoemission1,2,3. Here an electron is photoemitted from a metal into a semiconductor4,<a title="Di Bartolomeo, A. Graphene Schottky diodes: an experimental review of the rectifying graphene/semiconductor heterojunction. Phys. Rep. 606, 1–58 (2016)." href="https://www.nature.com/articles/s41566-019-0580-6#ref-CR5">5. While the photoelectric effect takes place within less than 100 attoseconds (1 as = 10−18 seconds)6,7, the attosecond timescale has so far not been measured for internal photoemission. Based on the new method CHArge transfer time MEasurement via Laser pulse duration-dependent saturation fluEnce determinatiON—CHAMELEON—we show that the atomically thin semimetal graphene coupled to bulk silicon carbide, forming a Schottky junction, allows charge transfer times as fast as (300 ± 200) as. These results are supported by a simple quantum mechanical model simulation. With the obtained cut-off bandwidth of 3.3 PHz (1 PHz = 1015 Hz) for the charge transfer rate, this semimetal/semiconductor interface represents a functional solid-state interface offering the speed and design space required for future light-wave signal processing.<br
Keywords: Nonlinear optics; Optical properties and devices; Optoelectronic devices and components; Ultrafast photonics

Carrier-envelope-phase-stable soliton-based pulse compression to 4.4 fs and ultraviolet generation at the 800 kHz repetition rate - Ermolov, Alexey; Heide, Christian; Dienstbier, Philip; Köttig, Felix; Tani, Francesco; Hommelhoff, Peter; Russell, Philip St. J. (Optics Letters, 2019)
In this Letter, we report the generation of a femtosecond supercontinuum extending from the ultraviolet to the near-infrared spectrum and detection of its carrier-envelope-phase (CEP) variation by f-to-2f interferometry. The spectrum is generated in a gas-filled hollow-core photonic crystal fiber, where soliton dynamics allows the CEP-stable self-compression of the optical parametric chirped-pulse amplifier pump pulses at 800 nm to a duration of 1.7 optical cycles, followed by dispersive wave emission. The source provides up to 1 μJ of pulse energy at the 800 kHz repetition rate, resulting in 0.8 W of average power, and it can be extremely useful, for example in strong-field physics, pump–probe measurements, and ultraviolet frequency comb metrology.<br
Keywords: supercontinuum generation; carrier-envelope-phase; hollow-core photonic crystal fiber; ultraviolet ultraviolet frequency comb metrology

CEP-stable generation of close to single-cycle and ultrashort UV pulses at 800 kHz repetition rate using a gas-filled hollow-core PCF - Ermolov, Alexey; Heide, Christian; Dienstbier, Philip; Tani, Francesco; Köttig, Felix; Hommelhoff, Peter; Russell, Philip St. John (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ultrashort laser pulses at high repetition rates are a fundamental tool in a wide range of applications in strong-field physics and attosecond science, where particular attention has to be given to the stability of the carrier to envelope phase (CEP) of the ultrashort optical waveform [1]. Here we report the generation of close to single-cycle pulses with stable CEP at 800 kHz repetition rate, obtained via soliton-effect self-compression in a gas-filled kagomé-type hollow-core photonic crystal fibre (kagomé-PCF) [2]. In addition, we have measured for the first time the CEP stability of soliton-emitted dispersive waves (DWs) lying in the ultraviolet spectral region.
CRIS-Team Scopus Importer:2019-11-15

Coherent Electron Trajectory Control in Graphene - Heide, Christian; Higuchi, Takuya; Weber, Heiko B.; Hommelhoff, Peter (Physical Review Letters, 2018)
We investigate coherent electron dynamics in graphene, interacting with the electric field waveform of two orthogonally polarized, few-cycle laser pulses. Recently, we demonstrated that linearly polarized driving pulses lead to sub-optical-cycle Landau-Zener quantum path interference by virtue of the combination of intraband motion and interband transition [Higuchi et al., Nature 550, 224 (2017)]. Here we introduce a pulsed control laser beam, orthogonally polarized to the driving pulses, and observe the ensuing electron dynamics. The relative delay between the two pulses is a tuning parameter to control the electron trajectory, now in a complex fashion exploring the full two-dimensional reciprocal space in graphene. Depending on the relative phase, the electron trajectory in the reciprocal space can, e.g., be deformed to suppress the quantum path interference resulting from the driving laser pulse. Intriguingly, this strong-field-based complex matter wave manipulation in a two-dimensional conductor is driven by a high repetition rate laser oscillator, rendering unnecessary complex and expensive amplified laser system

Electron dynamics in graphene reaching the light-field-driven regime - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2022-04-14

Electronic Coherence and Coherent Dephasing in the Optical Control of Electrons in Graphene - Heide, Christian; Eckstein, Timo; Boolakee, Tobias; Gerner, Constanze; Weber, Heiko B.; Franco, Ignacio; Hommelhoff, Peter (Nano Letters, 2021)
Electronic coherence is of utmost importance for the access and control of quantum-mechanical solid-state properties. Using a purely electronic observable, the photocurrent, we measure a lower bound of the electronic coherence time of 22 ± 4 fs in graphene. The photocurrent is ideally suited to measure electronic coherence, as it is a direct result of coherent quantum-path interference, controlled by the delay between two ultrashort two-color laser pulses. The maximum delay for which interference between the population amplitude injected by the first pulse interferes with that generated by the second pulse determines the electronic coherence time. In particular, numerical simulations reveal that the experimental data yields a lower bound on the electronic coherence time, masked by coherent dephasing due to the broadband absorption in graphene. We expect that our results will significantly advance the understanding of coherent quantum control in solid-state systems ranging from excitation with weak fields to strongly driven system
Keywords: graphene; quantum-path interference; electronic coherence time; quantum control

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec

Interaction of carrier envelope phase-stable laser pulses with graphene:the transition from the weak-field to the strong-field regime - Heide, Christian; Boolakee, Tobias; Higuchi, Takuya; Weber, Heiko B.; Hommelhoff, Peter (New Journal of Physics, 2019)
Ultrafast control of electron dynamics in solid state systems has recently found particular attention. By increasing the electric field strength of laser pulses, the light-matter interaction in solids might turn from a perturbative into a novel non-perturbative regime, where interband transitionsfrom the valence to the conduction band become strongly affected by intraband motion. We have demonstrated experimentally and numerically that this combined dynamics can be controlled in graphene with the electric field waveform of phase-stabilized few-cycle laser pulses. Here we show new experimental data and matching simulation results at comparably low optical fields, which allows us to focus on the highly interesting transition regime where the light-matter interaction turns from perturbative to non-perturbative. We find a 5th order power-law scaling of the laser induced waveform-dependent current at low optical fields, which breaks down for higher optical fields, indicating the transitio
Keywords: Ultrafast control of electron dynamics; graphene; intraband motion; transition regime

Landau-Zener-Stückelberg interferometer on attosecond timescales in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
When solids are exposed to intense optical fields, the intraband electron motion may influence interband transitions, potentially causing a transition of light-matter interaction from a quantum (photon-driven) regime to a semi-classical (field-driven) regime. We demonstrate this transition in monolayer graphene. We observe a carrier-envelope-phasedependent current in graphene irradiated with phase-stable two-cycle laser pulses, showing a striking reversal of the current direction as a function of the driving field amplitude at ∼2 V/nm. This reversal indicates the transition into the field-driven (or strong-field) regime. We show furthermore that in this regime electron dynamics are governed by suboptical-cycle Landau-Zener-Stückelberg interference, comprised of coherent repeated Landau-Zener transitions. We expect these results to have direct ramifications for light-wave driven electronics in graphene.
CRIS-Team Scopus Importer:2022-04-14
Keywords: attosecond physics; grapheme; light-field electronics; strong-field physics

Length-dependence of light-induced currents in graphene - Boolakee, Tobias; Heide, Christian; Wagner, Fabian; Ott, Christian; Schlecht, Maria-Theresa; Ristein, Jürgen; Weber, Heiko B.; Hommelhoff, Peter (Journal of Physics B-Atomic Molecular and Optical Physics, 2020)
We investigate the transport of optically injected currents in graphene, a (semi-) metal with exceptional optical and electronic properties. We have recently shown that ultrashort laser pulses with low temporal symmetry drive coupled intraband motion and interband (Landau-Zener) transitions resulting in residual ballistic currents in graphene. Here we show experimentally how this current scales as a function of the distance between the light-induced current injection region and the adjacent metal contact electrodes and propose an approach to model the results based on diffusive and field driven charge transport. We expect this study to contribute to ongoing discussions on the propagation of light-field-controlled currents, a requirement for future lightwave electronics, operating at petahertz clock rate

Light-field control of real and virtual charge carriers - Boolakee, Tobias; Heide, Christian; Garzón-Ramírez, Antonio; Weber, Heiko B.; Franco, Ignacio; Hommelhoff, Peter (Nature, 2022)
Light-driven electronic excitation is a cornerstone for energy and information transfer. In the interaction of intense and ultrafast light fields with solids, electrons may be excited irreversibly, or transiently during illumination only. As the transient electron population cannot be observed after the light pulse is gone, it is referred to as virtual, whereas the population that remains excited is called real1,<a title="Yamanishi, M. Field-induced optical nonlinearity due to virtual transitions in semiconductor quantum well structures. Phys. Rev. Lett. 59, 1014–1017 (1987)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR2">2,3,4. Virtual charge carriers have recently been associated with high-harmonic generation and transient absorption5,<a title="Schlaepfer, F. et al. Attosecond optical-field-enhanced carrier injection into the GaAs conduction band. Nat. Phys. 14, 560–564 (2018)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR6">6,<a title="Jürgens, P. et al. Origin of strong-field-induced low-order harmonic generation in amorphous quartz. Nat. Phys. 16, 1035–1039 (2020)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR7">7,8, but photocurrent generation may stem from real as well as virtual charge carriers9,<a title="Higuchi, T., Heide, C., Ullmann, K., Weber, H. B. & Hommelhoff, P. Light-field-driven currents in graphene. Nature 550, 224–228 (2017)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR10">10,11,12,<a title="Garzón-Ramírez, A. J. & Franco, I. Symmetry breaking in the Stark control of electrons at interfaces (SCELI). J. Chem. Phys. 153, 044704 (2020)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR13">13,<a title="Hanus, V. et al. Light-field-driven current control in solids with pJ-level laser pulses at 80 MHz repetition rate. Optica 8, 570 (2021)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR14">14. However, a link between the generation of the carrier types and their importance for observables of technological relevance is missing. Here we show that real and virtual charge carriers can be excited and disentangled in the optical generation of currents in a gold–graphene–gold heterostructure using few-cycle laser pulses. Depending on the waveform used for photoexcitation, real carriers receive net momentum and propagate to the gold electrodes, whereas virtual carriers generate a polarization response read out at the gold–graphene interfaces. On the basis of these insights, we further demonstrate a proof of concept of a logic gate for future lightwave electronics. Our results offer a direct means to monitor and excite real and virtual charge carriers. Individual control over each type of carrier will markedly increase the integrated-circuit design space and bring petahertz signal processing closer to reality<a title="Krausz, F. & Stockman, M. I. Attosecond metrology: from electron capture to future signal processing. Nat. Photon. 8, 205–213 (2014)." href="https://www.nature.com/articles/s41586-022-04565-9#ref-CR15">15,16</sup
Keywords: light-driven electronics; graphene; heterostructures; virtual and real charge carriers; ultrafast

Light-field driven currents in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (arXiv, 2016)
Ultrafast electron dynamics in solids under strong optical fields has recently found particular attention. In dielectrics and semiconductors, various light-field-driven effects have been explored, such as high-harmonic generation, sub-optical-cycle interband population transfer and nonperturbative increase of transient polarizability. In contrast, much less is known about field-driven electron dynamics in metals because charge carriers screen an external electric field in ordinary metals. Here we show that atomically thin monolayer Graphene offers unique opportunities to study light-field-driven processes in a metal. With a comparably modest field strength of up to 0.3 V/Å, we drive combined interband and intraband electron dynamics, leading to a light-field-waveform controlled residual conduction current after the laser pulse is gone. We identify the underlying pivotal physical mechanism as electron quantum-path interference taking place on the 1-femtosecond (10-15s)timescale. The process can be categorized as Landau-Zener-St"uckelberg interferometry. These fully coherent electron dynamics in graphene take place on a hitherto unexplored timescale faster than electron-electron scattering (tens of femtoseconds) and electron-phonon scattering (hundreds of femtoseconds). These results broaden the scope of light-field control of electrons in solids to an entirely new and eminently important material class – metals – promising wide ramifications for band structure tomography and light-field-driven electronics.

Light-field-driven currents in graphene - Higuchi, Takuya; Heide, Christian; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (Nature, 2017)
The ability to steer electrons using the strong electromagnetic field of light has opened up the possibility of controlling electron dynamics on the sub-femtosecond (less than 10−15 seconds) timescale. In dielectrics and semiconductors, various light-field-driven effects have been explored, including high-harmonic generation1, 2, 3, 4, sub-optical-cycle interband population transfer5 and the non-perturbative change of the transient polarizability6, 7. In contrast, much less is known about light-field-driven electron dynamics in narrow-bandgap systems or in conductors, in which screening due to free carriers or light absorption hinders the application of strong optical fields6, 8. Graphene is a promising platform with which to achieve light-field-driven control of electrons in a conducting material, because of its broadband and ultrafast optical response, weak screening and high damage threshold9, 10. Here we show that a current induced in monolayer graphene by two-cycle laser pulses is sensitive to the electric-field waveform, that is, to the exact shape of the optical carrier field of the pulse, which is controlled by the carrier-envelope phase, with a precision on the attosecond (10−18 seconds) timescale. Such a current, dependent on the carrier-envelope phase, shows a striking reversal of the direction of the current as a function of the driving field amplitude at about two volts per nanometre. This reversal indicates a transition of light–matter interaction from the weak-field (photon-driven) regime to the strong-field (light-field-driven) regime, where the intraband dynamics influence interband transitions. We show that in this strong-field regime the electron dynamics are governed by sub-optical-cycle Landau–Zener–Stückelberg interference11, composed of coherent repeated Landau–Zener transitions on the femtosecond timescale. Furthermore, the influence of this sub-optical-cycle interference can be controlled with the laser polarization state. These coherent electron dynamics in graphene take place on a hitherto unexplored timescale, faster than electron–electron scattering (tens of femtoseconds) and electron–phonon scattering (hundreds of femtoseconds)12, 13, 14. We expect these results to have direct ramifications for band-structure tomography2 and light-field-driven petahertz electronics8</sup

Light field-driven electron dynamics in 2D-materials - Boolakee, Tobias; Heide, Christian; Weber, Heiko B.; Hommelhoff, Peter (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Two dimensional materials such as graphene offer exceptional optical and electronic properties and are therefore predestined for light-field controlled electron dynamics inside of matter. In particular, graphene with its Dirac-cone dispersion relation represents an ideal two-level system where intricately coupled intra-band motion and inter-band (Landau-Zener) electron transitions can be driven under the influence of a strong electric field, i.e., above 2 V/nm [1] , [2]. Using carrier-envelope phase-controlled few-cycle laser pulses, we have demonstrated such repeated Landau-Zener transitions to be driven fully coherently between valence and conduction band, separated only by half an optical period of 1.3 femtoseconds.
CRIS-Team Scopus Importer:2021-10-29

Lightwave-controlled electron dynamics in graphene - Heide, Christian; Higuchi, Takuya; Ullmann, Konrad; Weber, Heiko B.; Hommelhoff, Peter (205, 2019)
We demonstrate that currents induced in graphene by ultrashort laser pulses are sensitive to the exact shape of the electric-field waveform. By increasing the field strength, we found a transition of the light–matter interaction from the weak-field to the strong-field regime at around 2 V/nm, where intraband dynamics influence interband transitions. In this strong-field regime, the light-matter interaction can be described by the wavenumber trajectories of electrons in the reciprocal space. For linearly polarized light the electron dynamics are governed by repeated sub-optical-cycle Landau-Zener transitions between the valence- and conduction band, resulting in Landau-Zener-Stuckelberg interference, whereas for circular polarized light this interference is supresse

Linear magnetoresistance in mosaic-like bilayer graphene - Kißlinger, Ferdinand; Ott, Christian; Heide, Christian; Kampert, Erik; Butz, Benjamin; Spiecker, Erdmann; Shallcross, Sam; Weber, Heiko B. (Nature Physics, 2015)
The magnetoresistance of conductors usually has a quadratic dependence on magnetic field(1), however, examples exist of non-saturating linear behaviour in diverse materials(2-6). Assigning a specific microscopic mechanism to this unusual phenomenon is obscured by the co-occurrence and interplay of doping, mobility fluctuations and a polycrystalline structure(7,8). Bilayer graphene has virtually no doping fluctuations, yet provides a built-in mosaic tiling due to the dense network of partial dislocations(9,10). We present magnetotransport measurements of epitaxial bilayer graphene that exhibits a strong and reproducible linear magnetoresistance that persists to B = 62 T at and above room temperature, decorated by quantum interference effects at low temperatures. Partial dislocations thus have a profound impact on the transport properties in bilayer graphene, a system that is frequently assumed to be dislocation-free. It further provides a clear and tractable model system for studying the unusual properties of mosaic conductors.

Optical current generation in graphene: CEP control vs. ω + 2ω control - Heide, Christian; Boolakee, Tobias; Eckstein, Timo; Hommelhoff, Peter (Nanophotonics, 2021)
The injection of directional currents in solids with strong optical fields has attracted tremendous attention as a route to realize ultrafast electronics based on the quantum-mechanical nature of electrons at femto- to attosecond timescales. Such currents are usually the result of an asymmetric population distribution imprinted by the temporal symmetry of the driving field. Here we compare two experimental schemes that allow control over the amplitude and direction of light-field-driven currents excited in graphene. Both schemes rely on shaping the incident laser field with one parameter only: either the carrier-envelope phase (CEP) of a single laser pulse or the relative phase between pulses oscillating at angular frequencies ω and 2ω, both for comparable laser parameters. We observe that the efficiency in generating a current via two-color-control exceeds that of CEP control by more than two orders of magnitude (7 nA vs. 18 pA), as the ω + 2ω field exhibits significantly more asymmetry in its temporal shape. We support this finding with numerical simulations that clearly show that two-color current control in graphene is superior, even down to single-cycle pulse durations. We expect our results to be relevant to experimentally access fundamental properties of any solid at ultrafast timescales, as well as for the emerging field of petahertz electronics.<br

Strong-Field Bloch Electron Interferometry for Band-Structure Retrieval - Weitz, Tobias; Heide, Christian; Hommelhoff, Peter (Physical Review Letters, 2024)
When Bloch electrons in a solid are exposed to a strong optical field, they are coherently driven in their respective bands where they acquire a quantum phase as the imprint of the band shape. If an electron approaches an avoided crossing formed by two bands, it may be split by undergoing a Landau-Zener transition. We here employ subsequent Landau-Zener transitions to realize strong-field Bloch electron interferometry, allowing us to reveal band structure information. In particular, we measure the Fermi velocity (band slope) of graphene in the vicinity of the K points as (1.07 ± 0.04) nm*fs^(−1). We expect strong-field Bloch electron interferometry for band structure retrieval to apply to a wide range of material systems and experimental conditions, making it suitable for studying transient changes in band structure with femtosecond temporal resolution at ambient condition
Keywords: Ballistic transport; Band gap; Density of states; Electrical conductivity; Optical interactions with surfaces; Photocurrent; Photogalvanic effect; Stark effect

Sub-cycle temporal evolution of light-induced electron dynamics in hexagonal 2D materials - Heide, Christian; Boolakee, Tobias; Higuchi, Takuya; Hommelhoff, Peter (JPhys Photonics, 2020)
Two-dimensional materials with hexagonal symmetry such as graphene and transition metal dichalcogenides are unique materials to study light-field-controlled electron dynamics inside of a solid. Around the K-point, the dispersion relation represents an ideal system to study intricately coupled intraband motion and interband (Landau-Zener) transitions driven by the optical field of phase-controlled few-cycle laser pulses. Based on the coupled nature of the intraband and interband processes, we have recently observed in graphene repeated coherent Landau-Zener transitions between valence and conduction band separated by around half an optical period of 1.3 fs [Higuchi et al., Nature 550, 224 (2017)]. Due to the low temporal symmetry of the applied laser pulse, a residual current density and a net electron polarization are formed. Here we show extended numerical data on the temporal evolution of the conduction band population of 2D materials with hexagonal symmetry during the light-matter interaction, yielding deep insights to attosecond-fast electron dynamics. In addition, we show that a residual ballistic current density is formed, which strongly increases when a band gap is introduced. Both, the sub-cycle electron dynamics and the resulting residual current are relevant for the fundamental understanding and future applications of strongly driven electrons in two-dimensional materials, including graphene or transition metal dichalcogenide monolayer

Ultrafast Strong-Field Electron Emission and Collective Effects at a One-Dimensional Nanostructure - Paschen, Timo; Roussel, Ryan; Seiffert, Lennart; Kruse, Björn; Heide, Christian; Dienstbier, Philip; Mann, Joshua; Rosenzweig, James; Fennel, Thomas; Hommelhoff, Peter (ACS Photonics, 2023)
Enhanced near-fields at metallic nanostructures enable the generation of ultrafast nanometric electron pulses and the investigation of fundamental ultrafast dynamics in electron emission. Here we show strong-field induced photoemission from a nanometer-sharp tungsten-covered silicon nanoblade and report the systematic measurement of intensity-dependent electron energy spectra and yields. The observed plateau and cutoff features in the electron spectra indicate the presence of elastic electron rescattering in the enhanced near-fields at the surface of the one-dimensional nanostructure. For the first time, we can hence observe strong-field features from a one-dimensional object, as opposed to zero-dimensional needle tips employed so far. A comparison with results from classical and quantum simulations reveals that the extended geometry of the nanoblades and a cascaded near-field enhancement due to surface roughness leads to a broad energy distribution and high electron energies. A systematic analysis of the electron yield demonstrates nonlinear photoemission at moderate laser intensities and a clear transition to a regime with linear intensity dependence. This distinct feature is interpreted as the onset of space-charge trapping. The presented one-dimensional nanostructure enables us to generate above keV electrons without noticeable target damage and more than 13000 electrons per laser pulse, which is of utmost interest for novel classes of ultrafast photocathodes.
CRIS-Team Scopus Importer:2023-03-03
Keywords: FDTD; one-dimensional; photoemission; space-charge; strong-field; TDSE; ultrafast